3D-printed porous tantalum for acetabular reconstruction in complex primary arthroplasty and revision of hip - Wang, Zonghan; Wang, Ze; Gu, Lingchuan; Zhang, Ying; Su, Tiao; Luo, Jiangming; Huang, Chengjun; Gong, Xiaoyuan; Peng, Yang; Chen, Guangxing (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionIn cases of hip joint damage, such as osteoarthritis (OA), rheumatoid arthritis (RA), avascular necrosis, or hip fractures, total hip arthroplasty (THA) is a critical surgical intervention. For individuals whose hip abnormalities stem from congenital issues, injuries, or previous operations, this procedure can encounter considerable obstacles, including complex bone defects, soft tissue deficiencies, and an increased risk of infections, which may result in poor alignment, joint instability, and higher need for revisions. This study explored the application of personalized, three-dimensional (3D)-printed porous tantalum buttresses designed specifically for acetabular reconstruction. Renowned for its compatibility with human biology, tantalum facilitates superior integration with natural bone.MethodsThe development process started with the generation of meticulous computer-aided design (CAD) models, derived from preoperative imaging techniques such as computed tomography (CT) scans and (magnetic resonance imaging) MRIs, which allowed for the creation of components precisely matching each patient’s unique anatomical structure. The 3D-printed porous tantalum buttresses were made by cutting-edge additive manufacturing methods. The porosity of the tantalum structure promoted the growth of new bone tissue into the implant, improving its stability and durability. During surgeries, the buttress was positioned to reconstruct the acetabulum, laying a solid foundation for the artificial hip joint.ResultsThe results of our study showed that all surgeries were successfully completed with no significant vascular or nerve damage. Postoperative evaluations showed that the buttress had excellent biomechanical function and firm fixation, with a large amount of bone ingrowth, improving the fitness and performance of the implant while reducing the possibility of subsequent problems such as loosening or dislocation.DiscussionThis innovative technique has great potential in clinical practice for better outcomes and quality of life for patients with complex hip deformities.